Function and regulation of cGAS-STING signaling in infectious diseases - Du, Yang; Hu, Zhiqiang; Luo, Yien; Wang, Helen Y.; Yu, Xiao; Wang, Rong-Fu (Frontiers in Immunology, 2023)
The efficacious detection of pathogens and prompt induction of innate immune signaling serves as a crucial component of immune defense against infectious pathogens. Over the past decade, DNA-sensing receptor cyclic GMP-AMP synthase (cGAS) and its downstream signaling adaptor stimulator of interferon genes (STING) have emerged as key mediators of type I interferon (IFN) and nuclear factor-kB (NF-kB) responses in health and infection diseases. Moreover, both cGAS-STING pathway and pathogens have developed delicate strategies to resist each other for their survival. The mechanistic and functional comprehension of the interplay between cGAS-STING pathway and pathogens is opening the way for the development and application of pharmacological agonists and antagonists in the treatment of infectious diseases. Here, we briefly review the current knowledge of DNA sensing through the cGAS-STING pathway, and emphatically highlight the potent undertaking of cGAS-STING signaling pathway in the host against infectious pathogenic organisms.